KAMPUNG MASPATI AS A SUSTAINABLE KAMPUNG IN SURABAYA CITY - Emiria Letfiani; Arlita Widyasari (Journal of Architecture&ENVIRONMENT, 2015)
This paper discusses the role of kampung in sustainable urban development. Because two third of the city's population live in kampung, and most of the population are people with low and middle incomes. The kampung should be able to contribute in the development of the city. Kampung Maspati RT (Neighborhood Board) 03 RW (Citizen Board) 08 as the object of this research is the winner of ‘Best of the Best kampung’ in Green and Clean 2015 competition for developing category. This kampung was once a slum kampung, but over time, local community start to increase the quality of the kampung. The aim of this study is to demonstrate empirically that the kampung Maspati is able to improve the quality of environment, social and economic aspects. The method used in this study is descriptive qualitative. The method of data collection are observation and interviews which were done directly to the residents and also to the local environment guide. Document action also used such as photography. Results of this study shows that kampung Maspati deserves the title Best of the Best Surabaya of Green and Clean 2015 for developing category, because it has managed to improve the quality of the environment, although it is still not holistically. However, it is indirectly give some impacts in improving the economy and social welfare. Overall, the communities of kampung Maspati have made it out of the slum and contributes to the development of sustainable cities.